Co-housing as a Sustainable Architecture to Support the City’s Particular Community - Hendrico Firzandy; Antony Sihombing; Achmad Hery Fuad; Mastura Adam (International Journal of Technology, 2024)
This paper discusses co-housing and its role as sustainable architecture to support various aspects of the life of communities and the environment. This research is important because the potential of co-housing settlements to improve the social and mental well-being of their residents has not been widely discussed. In addition, housing that uses sustainable technology tends to be very expensive, which, in the end, makes it more difficult for cultural communities to access settlements. For this reason, this study aims to demonstrate how the co-housing concept can address the issues mentioned earlier. To achieve this, a qualitative approach is employed, with the Miss Tjitjih (MT) community selected as the case study. The MT community was chosen because it has been living in co-housing concept housing for more than four decades. Open-ended questions were given to reveal opinions from the participant's side. The answers from the participants are then analyzed with the help of Nvivo. The results of the analysis are then grouped to obtain a code that explains the role of co-housing for this community. The resulting diagram reveals the role of co-housing as a settlement model that can answer various problems of cultural communities in the city.